Effect Size Model Open Ended Learning on Creative Thinking Ability of Elementary School Students - Dwi Fajarwati; Mimin Ninawati (Jurnal Paedagogy, 2023)
This study aims to analyze the model Open Ended Learning to improve the creative thinking skills of elementary school students in mathematics. The research method used was an experiment with the One Group Pretest Posttest Design. The population of this study was all 23 students of grade IV, with the sampling technique used was saturated sampling. The research instrument used a written test in the form of an essay. The data analysis technique of this study used statistics with SPSS 25.0 for Windows normality test Kolmogorov-Smirnov, One-Way Anova, Paired t-test, and Effect Size. The results of this study indicated a positive influence of Open-Ended Learning on increasing students' mathematical creative thinking skills. It is evidenced by the results of the Cohen's Effect Size test, which was 2.930 with the range of criteria in the Cohen's, namely the size was more significant than 1.00. It was classified as high based on the effect size, indicating that the use of the Open-Ended Learning learning model has a strong influence on the improvement of students' mathematical creative thinking skills.